2019
DOI: 10.1016/j.ihj.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): An independent, genetic, and causal factor for cardiovascular disease and acute myocardial infarction

Abstract: Lipoprotein(a) [Lp(a)] is a circulating lipoprotein, and its level is largely determined by variation in the Lp(a) gene (LPA) locus encoding apo(a). Genetic variation in the LPA gene that increases Lp(a) level also increases coronary artery disease (CAD) risk, suggesting that Lp(a) is a causal factor for CAD risk. Lp(a) is the preferential lipoprotein carrier for oxidized phospholipids (OxPL), a proatherogenic and proinflammatory biomarker. Lp(a) adversely affects endothelial function, inflammation, oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 202 publications
(404 reference statements)
0
57
0
2
Order By: Relevance
“…Lp(a) is an independent risk factor for CVD, and levels are primarily genetically determined, with a small influence of environmental factors. Approximately, 20-30% of the world's population have an elevated Lp(a), defined as > 50 mg/dL or > 125 nmol/L [17]. There are exceptions to generally stable levels, including a stressful environment such as sepsis, in which Lp(a) levels are acutely elevated [18,19].…”
Section: Lp(a) and Antifibrinolytic Effectsmentioning
confidence: 99%
“…Lp(a) is an independent risk factor for CVD, and levels are primarily genetically determined, with a small influence of environmental factors. Approximately, 20-30% of the world's population have an elevated Lp(a), defined as > 50 mg/dL or > 125 nmol/L [17]. There are exceptions to generally stable levels, including a stressful environment such as sepsis, in which Lp(a) levels are acutely elevated [18,19].…”
Section: Lp(a) and Antifibrinolytic Effectsmentioning
confidence: 99%
“…In the literature, lp(a) has been identified as an independent risk factor for vascular disease and subjects with lp(a) values above 30 mg/dL have an increased risk of developing early atherosclerotic disease [16]. While lp(a) levels are mainly under genetic control and are less affected than other lipoproteins by age, sex, weight, and diet, there are a few exogenous factors, such as physical exercise, estrogen therapy, and endstage renal failure, that affect lp(a) serum concentrations [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the three methods all suggested that there was no signi cant correlation between Lp(a) variation rate and NLR in diabetic population. Previous studies have shown that the level of Lp(a) is affected by genetic factors and is relatively stable within an individual with a small variation rate [29]. Therefore, in this study, it was also shown that the variation rate of lp(a) is relatively small, and the diabetic subgroup itself has long-term chronic low-grade in ammation, which makes the variation of lp(a) in this subgroup relatively The in uence of the level of in ammation is interfered by the in ammatory factors of diabetes, which weakens the correlation between the two.…”
Section: Discussionmentioning
confidence: 99%